Historical context, process, and development trends of pediatric thyroid cancer research: a bibliometric analysis - Song, Chang; Luo, Jia-Yuan; Pang, Yu-Yan; He, Rong-Quan; Li, Xiao-Jiao; Chen, Gang; Zhao, Chun-Yan; Qu, Ning; Chen, Yan-Mei; Yang, Li; Li, Bi-Qi; Shi, Lin (Frontiers in Oncology, 2024)
Objective At present, the structure of knowledge in the field of childhood thyroid cancer is not clear enough, and scholars lack a sufficient understanding of the developing trends in this field, which has led to a shortage of forward-looking outputs. The purpose of this research is to help scholars construct a complete knowledge framework and identify current challenges, opportunities, and development trends. Methods We searched the literature in the Web of Science Core Collection database on August 7, 2023 and extracted key information from the top 100 most cited articles, such as the countries, institutions, authors, themes, and keywords. We used bibliometric tools such as bibliometrix, VOSviewer, and CiteSpace for a visualization analysis and Excel for statistical descriptions. Results The top 100 most cited articles fluctuated over time, and the research was concentrated in European countries, the United States, and Japan, among which scientific research institutions and scholars from the United States made outstanding contributions. Keyword analysis revealed that research has shifted from simple treatment methods for pediatric thyroid cancer (total thyroidectomy) and inducing factors (the Chernobyl power station accident) to the clinical applications of genetic mutations (such as the BRAF and RET genes) and larger-scale genetic changes (mutation studies of the DICER1 gene). The thematic strategy analysis showed an increasing trend towards the popularity of fusion oncogenes, while the popularity of research on traditional treatments and diagnostics has gradually declined. Conclusion Extensive research has been conducted on the basic problems of pediatric thyroid cancer, and there has been significant outputs in the follow-up and cohort analysis of conventional diagnostic and treatment methods. However, these methods still have certain limitations. Therefore, scholars should focus on exploring fusion genes, the clinical applications of molecular targets, and novel treatment methods. This study provides a strong reference for scholars in this field.